Neoarchean crustal shear zones and implications of shear indicators in tectonic evolution of Bundelkhand craton, central India - S C Bhatt; Vinod K. Singh (JGEET: Journal of Geoscience, Engineering, Environment and Technology, 2019)
The gneisses and granitoids emplaced along E-W sub-vertical crustal shear zones are represented as important tectonic units in Bundelkhand craton of central India. The tonalite-trondhjemite-granodiorite (TTG) gneisses (3.5-3.2 Ga; oldest unit), and streaky to mafic gneisses structurally deformed in D 1 deformation. The metabasic, felsic, banded iron formation and metasedimentaries of greenstone complex exposed in central part, have characteristics of three sets of folding (F 1 -F 3 ). These gneisses associated with migmatite, amphibolite, quartzite, and schist were evolved in D 2 compressive phase, which are not occurring in northern part of craton. The K-rich Neoarchean granitoids (2.6-2.49 Ga) were intruded as granitic complex (D 3 magmatic phase) and the E-W strike-slip Raksa-Garhmau shear zone reported as important tectonic unit, were evolved in a syn-to post-tectonic D 3 phase. The dolerite dykes (ca. 2.0 Ga) were emplaced along NW-SE fractures in extension setting during D 4 magmatic event. The NE-SW riedel shears occupied by giant quartz veins (reefs) evolved in Paleoproterozoic during D 5 endogenic activity.